Gender Differences in Strategic Behaviour under Competitive Pressure: Evidence on Omission Patterns in University Entrance Examinations - Tuomas Pekkarinen (Institute for the Study of Labor (IZA), 2014)
This paper studies gender differences in performance in university entrance examinations. We exploit data from the exams that the nine Finnish universities providing education in economics and business use to choose their students. These exams are multiple choice tests where wrong answers are penalized by minus points and omissions yield zero points. This scoring rule means that the number of omitted items will affect the probability of entry. The strategic setting of the applicants varies depending on the university where she is applying to and on the amount of starting points that she is rewarded based on her high school success. The results show that, controlling for starting points, women perform worse than men in the entrance exam and are less likely to gain entry. Women also omit more items in the exam. Using the Rasch Model to derive the predicted probabilities of answering items correctly for each applicant, we show that women deviate more from the number of answered items that would maximise the predicted probability of entry than men and that they do so because they answer to too few items.
Keywords: J16; I21; I23; 330; gender differences; competition; multiple choice exams